Higher serum apolipoprotein B level will reduce the bone mineral density and increase the risk of osteopenia or osteoporosis in adults - Zhu, RunJiu; Xu, Yuan; Wang, ZhaoFu; Li, Hui; Song, MingRui; Wan, HaoYang; Yang, Hong; Zhang, Xin; Chai, Yu; Yu, Bin (Frontiers in Cell and Developmental Biology, 2022)
Objective: There is very limited evidence in the NHANES database linking serum apolipoprotein B and lumbar bone mineral density (BMD) in adults aged 20–59 years. There are few studies associating apolipoprotein B concentrations with BMD, and there is some debate about the association between obesity and BMD. Therefore, the purpose of this study was to determine the association between serum apolipoprotein B concentrations and lumbar spine BMD in adults aged 20–59 years and to predict its association with risk of osteopenia or osteoporosis. Methods: A cross-sectional study of the entire US ambulatory population was conducted using data from the National Health and Nutrition Examination Survey (NHANES) database. Weighted multiple regression equation models were used to assess the association between serum apolipoprotein B and lumbar BMD. A logistic weighted regression model was used to assess the association between serum apolipoprotein B concentrations and risk of osteopenia or osteoporosis. Subsequent stratified analyses were performed to refine the primary population of association. Results: Our study showed a significant negative association between serum apolipoprotein B concentration and lumbar BMD and a significant positive association with the risk of osteoporosis or osteopenia in the total population. After stratifying by sex, age and race, we concluded differently. The association of serum apolipoprotein B concentration with lumbar spine BMD and risk of osteopenia or osteoporosis was significant in male, but not in female. After stratification by age, the negative association between serum apolipoprotein B concentrations and lumbar BMD and the positive association with risk of osteopenia or osteoporosis was more significant in the 30–39 and 50–59 years age groups. When stratified by race, serum apolipoprotein B concentrations were significantly negatively associated with lumbar BMD and positively associated with risk of osteopenia or osteoporosis in Mexican American and non-Hispanic black populations. Thus, these findings suggest that these associations are influenced by sex, age, and race, respectively. Conclusion: Our results suggest that the association between serum apolipoprotein B levels and the risk of lumbar BMD and osteopenia or osteoporosis varies by sex, age, and race. In men, elevated serum apolipoprotein B levels were negative for bone quality. Elevated serum apolipoprotein B levels in the age groups 30–39 and 50–59 years also had a negative effect on bone quality. In the Mexican American and Non-Hispanic Black populations, elevated serum apolipoprotein B levels also had a significant negative effect on bone quality.